2018
DOI: 10.26719/2018.24.7.672
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of health research institutions in knowledge translation in the Eastern Mediterranean Region

Abstract: There is still misalignment between national health research priorities and actual research production, and KT activities are still rarely undertaken by institutions in the EMR. National governments and international funding agencies are called to support research production and translation in the EMR. Institutions and researchers are also called to produce policy-relevant research and be responsive to the needs and priorities of policy-makers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Twelve studies reported on the KT capacity of LMIC researchers and research institutions based on researchers' self-reports and reviews of institutional documents [31][32][33][34][35][36][37][38][39][40][41][42]. About half of the studies were conducted in one or several countries in the Eastern Mediterranean Region [31,33,36,[38][39][40]. Three studies focused on sub-Saharan Africa (a total of six countries) [32,34,42] and three studies were global [35,41] or covered more than one LMIC region, including sub-Saharan Africa and the Eastern Mediterranean Region [37].…”
Section: Kt Capacity Of Researchers' and Research Institutionsmentioning
confidence: 99%
“…Twelve studies reported on the KT capacity of LMIC researchers and research institutions based on researchers' self-reports and reviews of institutional documents [31][32][33][34][35][36][37][38][39][40][41][42]. About half of the studies were conducted in one or several countries in the Eastern Mediterranean Region [31,33,36,[38][39][40]. Three studies focused on sub-Saharan Africa (a total of six countries) [32,34,42] and three studies were global [35,41] or covered more than one LMIC region, including sub-Saharan Africa and the Eastern Mediterranean Region [37].…”
Section: Kt Capacity Of Researchers' and Research Institutionsmentioning
confidence: 99%
“…There are increasing initiatives and projects related to knowledge translation in general and CPGs in particular nationally and regionally [9,27,28]. The World Health Organization of the Regional O ce of the Eastern Mediterranean is promoting and supporting all advances in the development, adaptation, and implementation of CPGs at the regional level [28]. Furthermore, 'National guidelines' are core components of the 'Model of Care' of the new Saudi Arabian National Healthcare Plan [30,31].…”
Section: Declarationsmentioning
confidence: 99%
“…Despite these examples, a study of 10 Arab countries reflected various levels of development and resources in their national health research systems, while only three countries reported setting national health research priorities (21). While there may be a need for further national level action on identification of research priorities (21)(22), there are questions on whether previous priority settings have resulted in affirmative action on guiding health research.…”
mentioning
confidence: 99%
“…A recent study involving over 200 institutions in the EMR indicated that only half reported conduct ing research priority-setting exercises, of which only 40% followed a standardized approach and involved policymakers and stakeholders in setting such priorities. In addition, only a quarter of institutions reported that they examine the extent to which health policy-makers utilize research results, and a similar number reported measuring the impact of their health research (22,24). Hence, there is still a misalignment between national health research priorities and actual research production and use (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation